2011
DOI: 10.1155/2011/137560
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Paracetamol, Chlorzoxazone and Diclofenac Sodium in Tablet Dosage Form by High Performance Liquid Chromatography

Abstract: A simple, precise and rapid isocratic reverse phase high performance liquid chromatographic method was developed for the simultaneous determination of paracetamol, chlorzoxazone and diclofenac sodium from tablet dosage form. The chromatographic separation was performed on an inertsil C18column (250 mm × 4.6 mm i.d 5 µm particle size). Mobile phase consisted of a mixture of phosphate buffer (0.02 M KH2PO4, pH adjusted to 3.7 using orthophosphoric acid), acetonitrile and methanol in the ratio of (25: 25: 50) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Various methods have been reported for the determination of mefenamic acid as pure and in dosages forms. These methods include titrimetric [9,10], chromatographic [11][12], luminescence [13], flow injection [14][15], electrometric [16], spectroflourometric [17][18] and spectrophotometric methods [19][20][21][22].…”
Section: Open Accessmentioning
confidence: 99%
“…Various methods have been reported for the determination of mefenamic acid as pure and in dosages forms. These methods include titrimetric [9,10], chromatographic [11][12], luminescence [13], flow injection [14][15], electrometric [16], spectroflourometric [17][18] and spectrophotometric methods [19][20][21][22].…”
Section: Open Accessmentioning
confidence: 99%
“…Literature review revealed that the three cited components were simultaneously determined in ternary mixture by HPLC, HPTLC [24][25][26][27][28][29] , and by simultaneous equation methods [30][31] . To our knowledge, chemometric techniques for simultaneous determination of these drugs have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods were developed for the simultaneous determination of DIC in binary combination with PAR or CHZ that include spectrophotometry [23][24][25], densitometry [26], voltammetry [27], and HPLC-UV [28,29]. Some methods were reported for the simultaneous determination of ternary combination of the three drugs based on densitometry [30,31] and HPLC-UV [32,33].…”
Section: Introductionmentioning
confidence: 99%